To divide the expression \( 56r - 12 \) by \( 4t \), you can break it down as follows:
-
First, separate the terms in the numerator: \[ \frac{56r - 12}{4t} = \frac{56r}{4t} - \frac{12}{4t} \]
-
Now, simplify each term:
- For the first term: \[ \frac{56r}{4t} = \frac{56}{4} \cdot \frac{r}{t} = 14 \cdot \frac{r}{t} = \frac{14r}{t} \]
- For the second term: \[ \frac{12}{4t} = \frac{12}{4} \cdot \frac{1}{t} = 3 \cdot \frac{1}{t} = \frac{3}{t} \]
-
Combine the simplified terms: \[ \frac{56r - 12}{4t} = \frac{14r}{t} - \frac{3}{t} \]
Thus, the quotient of \( \frac{56r - 12}{4t} \) is: \[ \frac{14r}{t} - \frac{3}{t} \]